The biome inventory – Standardizing global biogeographical land units. Issue 11 (16th August 2022) - Fischer, Jan‐Christopher; Walentowitz, Anna; Beierkuhnlein, Carl
Abstract: Motivation: The subdivision of the Earth's terrestrial surface into different biomes, ecozones, bio‐climatic realms or other large ecological land units is an essential reference for global biogeographical and ecological studies. Various classification schemes exist. These differ significantly in terms of the considered criteria for classification and the underlying methodology of class assignments. Evident divergences between global biome concepts are elusive, weakening hereon based analyses and assumptions. Compilation and standardization are essential for obtaining a framework that enables the comparison of different products. To address this need, we created a catalogue of standardized categorial biome maps comprising 31 different global products based on various methodological approaches. These products were processed individually to facilitate their use in large‐scale biogeographical and ecological analyses. Main types of variables contained: We provide a unified RasterStack containing 31 terrestrial biome and land‐cover classifications in different layers. Additional ancillary and processing information is allocated. Spatial location and grain: Global, 10 km × 10 km grain size in equal‐area Mollweide projection. Major taxa and level of measurement: Biomes, ecozones, bio‐climatic zones, and ecological land units. Software format: GeoTiff.